Performance versus height in Freestyle swimming in girls of 10 years - Tertuliano, Ivan Wallan; Pinto, Tatiana Galli Gonçalves; Silva, Caio Graco Simoni da; Mansoldo, Antonio Carlos; Machado, Afonso Antônio; Bonacella, Paulo Henrique (Manual Therapy, Posturology & Rehabilitation Journal, 2016)
Introduction: The Freestyle swimming is currently known as the fastest within the competitive environment. Objective: The objective of this study was to investigate the performance differences in Freestyle swimming of female children of 10 years old, relating total time of swim and stature, in a distance of 25 meters. Method: Participated in the study 10 female children of 10 years old. The task was to swim 25 meters, as fast as possible in Freestyle swimming and, beyond this measure, was used anthropometric measure related to height. Was conducted a Pearson Correlation test. Results: The results showed that the correlation is inversely proportional (negative), weak and non-significant, in other words, swim faster has no effect on the subjects’ height in the total duration of the swimming. Conclusion: The results indicate that there is no relationship between performance and height for girls of 10 years in the Freestyle swimming.